Pemasangan Paving Block Lapangan Olah Raga Sekolah Menengah Kejuruan Aviasi Branti - Lampung - Sukamto; Riyanto Saputro; Yenni Arnas; Ika Endrawijaya; Oka Fatra (Politeknik Penerbangan Indonesia Curug, 2021)
Aviasi Branti Vocational High School (SMK) - Lampung is a newly established vocational high school in the field of aviation with 95 students. Development of student abilities is not only limited to learning activities that support student competencies in the field of aviation, but also requires other abilities that support the achievement of key competencies. Good physical conditions and the interactions that occur while students carry out sports activities are one of the means that can beused to support students' main competencies. Politeknik Penerbangan Indonesia Curug through community service activities carried out the installation of paving blocks on the sports field at SMK Aviasi Branti - Lampung to improve the quality of the existing volleyball sports field facilities. Installation of paving blocks was carried out for 2 days involving the academic community of SMK Aviasi Branti - Lampung, assisted by local professionals. Theexistenceofpropervolleyballsportsfield facilities is expected to increase interaction between students, teachers and the community around the school as well as improve physical fitness in order to support the success of teaching and learning in schools.